PENGARUH RASIO PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - FAIZ AKBAR, RASYIDI (Jurnal Ilmu Manajemen (JIM), 2016)
This study aimed to test the independent variable (ROE, NPM, EPS, and DER) to the stock price on the manufacture companies listed on the Indonesia Stock Exchange in 2010-2014 partially. Data obtained from Indonesia Capital Market Directory. The sample in this study are 11 companies were taken by purposive sampling method. The data collection technique used is the technique of documentation. The method used in this study were using multiple linear regression. This research using classic assumption test analysis technique. These results indicate that not all the variables significantly influence stock prices . NPM and the DER has no effect on stock prices. Variable ROE and EPS significant positive effect on stock prices. Variable EPS positive and significant effect on stock prices. Keywords : Stock Price, ROE, NPM, EPS, DER.